Extreme Drought in the Brazilian Pantanal in 2019–2020: Characterization, Causes, and Impacts - Marengo, Jose A.; Cunha, Ana P.; Cuartas, Luz Adriana; Deusdará Leal, Karinne R.; Broedel, Elisangela; Seluchi, Marcelo E.; Michelin, Camila Miranda; De Praga Baião, Cheila Flávia; Chuchón Angulo, Eleazar; Almeida, Elton K.; Kazmierczak, Marcos L.; Mateus, Nelson Pedro António; et al. (Frontiers in Water, 2021)
The Pantanal region in South America is one of the world’s largest wetlands. Since 2019, the Pantanal has suffered a prolonged drought that has spelled disaster for the region, and subsequent fires have engulfed hundreds of thousands of hectares. The lack of rainfall during the summers of 2019 and 2020 was caused by reduced transport of warm and humid summer air from Amazonia into the Pantanal. Instead, a predominance of warmer and drier air masses from subtropical latitudes contributed to a scarcity of summer rainfall at the peak of the monsoon season. This led to prolonged extreme drought conditions across the region. This drought had severe impacts on the hydrology of the Pantanal. Hydrometric levels fell all along the Paraguay River. In 2020, river levels reached extremely low values, and in some sections of this river, transportation had to be restricted. Very low river levels affected the mobility of people and shipping of soybeans and minerals to the Atlantic Ocean by the Hidrovia -Paraná-Paraguai (Paraná-Paraguay Waterway). This study is directed to better understand the hydroclimatic aspects of the current drought in the Brazilian Pantanal and their impacts on natural and human systems. As a consequence of the drought, fires spread and affected natural biodiversity as well as the agribusiness and cattle ranching sectors. While fires had serious socioecological and economic consequences, we do not intend to investigate the effect of the downstream low-level waters on the Pantanal ecosystems or the drought in the risk of fire.